Outage statistics of double gamma–gamma random process and its application to cooperative optical wireless communication relay systems. (28th September 2021) - Dejanovic, Milan; Dubljanin, Milan; Kontrec, Natasa; Panic, Stefan; Djosic, Danijel; Stefanovic, Mihajlo
Abstract: This article investigates outage statistics of double gamma–gamma random variable (RV) modeled as the product of two independent and identically distributed gamma–gamma RVs. The outage closed‐form statistics in terms of the first‐order statistical measures (probability density function and cumulative distribution function) and the second‐order statistical measures (level crossing rate and average fade duration) by Laplace approximation integral (LAI) and exponential LAI are derived. The statistical results are directly related to the performance evaluation of dual‐hop as well as cooperative dual‐hop optical wireless communications over moderate to strong turbulence‐induced fading channels.